2006
DOI: 10.1159/000090502
|View full text |Cite
|
Sign up to set email alerts
|

Allergy Practice Worldwide: A Report by the World Allergy Organization Specialty and Training Council

Abstract: In 2004 the World Allergy Organization’s Specialty and Training Council conducted a survey of World Allergy Organization (WAO) member societies to obtain information about the status of the specialty of allergy worldwide. Responses were received from 33 countries, representing a population of 1.39 billion people, of whom it was estimated that 22% may suffer from some form of allergic disease. Allergy was reported by 23 respondents to be a certified or accredited specialty in their country, and the number of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 27 publications
0
109
0
6
Order By: Relevance
“…En general, la distribución de servicios asistenciales de alergología en la CM es mejor que en otras regiones españolas, próxi-mo a un alergólogo por cada 50.000 habitantes que recomienda la OMS, si bien en el mundo la razón alergólogo/habitantes es muy variable, oscilando incluso entre los 1:25 millones de algunos países africanos a 1:16.000 habitantes en Alemania 28 . En España, según datos del Ministerio de Sanidad de 2009 29 , solo La Rioja o Castilla-La Mancha alcanzarían el número recomendado mientras que en otras comunidades españolas como Navarra, Canarias o Extremadura se aproximaría al mismo y, sin embargo en algunas, se observan claras deficiencias.…”
Section: Discussionunclassified
“…En general, la distribución de servicios asistenciales de alergología en la CM es mejor que en otras regiones españolas, próxi-mo a un alergólogo por cada 50.000 habitantes que recomienda la OMS, si bien en el mundo la razón alergólogo/habitantes es muy variable, oscilando incluso entre los 1:25 millones de algunos países africanos a 1:16.000 habitantes en Alemania 28 . En España, según datos del Ministerio de Sanidad de 2009 29 , solo La Rioja o Castilla-La Mancha alcanzarían el número recomendado mientras que en otras comunidades españolas como Navarra, Canarias o Extremadura se aproximaría al mismo y, sin embargo en algunas, se observan claras deficiencias.…”
Section: Discussionunclassified
“…We feel that 'first level' competencies of the recent provisional statement by the World Allergy Organisation could be a useful resource for curriculum planning in this area. 14,20 This mapping exercise has highlighted some first-level competencies which are not currently taught in the Edinburgh medical curriculum, and will provide a springboard for debate about an appropriate undergraduate allergy curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Van Deventer (2007) found that some of the factors that led to poor outcomes in chronically ill patients in primary and rural care in South Africa were the lack of appropriate drugs and equipment and/ or lack of knowledge and/or clinical rigour of health care workers, lack of money to return for follow-up visits, which then led to defaulting on the treatment and a denial by patients of the seriousness of their chronic condition and its possible complications. In a study conducted by The World Allergy Organization Speciality and Training Council (Warner et al, 2006) it was found that the majority of allergic patients were seen by non-allergy-trained health workers. This situation is also true for South Africa (Pawankar et al, 2008;Potter et al, 2009).…”
Section: Literature Controlmentioning
confidence: 99%